Algorithms and Technologies for Multispectral, Hyperspectral, and Ultraspectral Imagery XX 2014
DOI: 10.1117/12.2050682
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of sand density from hyperspectral BRDF

Abstract: In past work 1 , we have shown that density effects in hyperspectral bi-directional reflectance function (BRDF) data are consistent in laboratory goniometer data, field goniometer measurements with the NRL Goniometer for Portable Hyperspectral Earth Reflectance (GOPHER), and airborne CASI-1500 hyperspectral imagery. Density effects in granular materials have been described in radiative transfer models 2,4,5 , and are known, for example, to influence both the overall level of reflectance as well as the size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Instead, reflectance increases as density decreases, with no inversion at any fill factor. This supports previous observation by Bachmann et al 5,11,12 that as density increases, multiple scattering returns leaving granular substances with optically contrasting mineral content are diminished, leading to an overall reduction in reflectance. Phase Angle Figure 11.…”
Section: Reflectance As a Function Of Phase Angle For Constant Azimuthsupporting
confidence: 91%
See 1 more Smart Citation
“…Instead, reflectance increases as density decreases, with no inversion at any fill factor. This supports previous observation by Bachmann et al 5,11,12 that as density increases, multiple scattering returns leaving granular substances with optically contrasting mineral content are diminished, leading to an overall reduction in reflectance. Phase Angle Figure 11.…”
Section: Reflectance As a Function Of Phase Angle For Constant Azimuthsupporting
confidence: 91%
“…5,11,12 Traditional radiative transfer theory, such as the model developed by Bruce Hapke 3 , suggests that the direct impact of an increase in granular material constituent density results in an increase in overall reflectance for fill factors up to approximately 0.52. 2,3 However, it has been shown that when a darker mineral fraction is present alongside larger, more translucent grains, reflectance decreases with higher density sands and increases with lower density composites.…”
Section: Introductionmentioning
confidence: 99%